Periodontitis Is Associated With Risk of Conventional Stent Restenosis: Pilot Case-Control Study - Osugue, Raphael [UNESP]; Castro dos Santos, Nidia C. [UNESP]; Araujo, Cassia F. [UNESP]; de Almeida, Flavio X.; Feres, Magda; Santamaria, Mauro P. [UNESP] (Frontiers, 2021)
Objectives: Percutaneous coronary angioplasty with stent implantation has been established as the main form of treatment of atherosclerosis. However, 16 to 44% of patients may evolve with stent restenosis. Periodontitis is an inflammatory condition associated with bacterial infection, that may lead to periodontal tissue destruction and tooth loss. This study aimed to evaluate the association between stent restenosis and periodontitis. Materials and Methods: Coronary angiography exams presenting stent imaging with and without restenosis were analyzed. Patients meeting the inclusion and exclusion criteria were selected and allocated in 2 groups: case (restenosis) and control (without restenosis). We evaluated if systemic and periodontal variables were predictors of restenosis (primary outcome) using a multivariable stepwise logistic regression. Additionally, we compared clinical and periodontal conditions between the control and case groups (secondary outcomes) using Chi-square test and ANOVA test. Results: Data from 49 patients (case n = 15; control n = 34) were analyzed. The results showed that stages III and IV periodontitis and lack of physical activity were significant predictors of stent restenosis (OR 5.82 and 5.98, respectively). Comparisons regarding the diagnosis of periodontal conditions between control and case groups did not present significant differences in the incidence of periodontitis and alveolar bone loss. Conclusion: Stages III and IV periodontitis increased the incidence of stent restenosis. These findings suggest that advanced stages of periodontal disease might lead to the occurrence of negative outcomes after coronary angioplasty with stent placement.
Keywords: atherosclerosis; cardiovascular disease; inflammation; periodontitis; stent restenosis